Drug treatment programmes in prison: longitudinal outcome evaluation, policy development and planning interventions. - COMISKEY, CATHERINE (My University, 2006)
The aim of this research is to evaluate a seven week abstinence-based drug treatment programme and to use this to assist policy makers in the planning and provision of future programmes. Seventy-nine clients were interviewed at two stages. Stage I, prior to the treatment programme, stage II, immediately after the treatment programme. A selected group of 20 clients were followed-up and interviewed at stage III, up to 24 months after the treatment programme. This latter sample of 20 clients consisted of eight prisoners who had re-offended and returned to prison, three prisoners who were still in prison serving their original sentence and nine prisoners who were out of prison. These 20 also participated in a more detailed quantitative and qualitative survey. All clients were prisoners at Mountjoy Prison, Dublin Ireland. In order to measure prisoner's criminogenic attitudes and needs the Crime Pics II instrument was used. This is a semantic differential scale which measures attitudes toward offending behaviour. It includes a problem checklist which can be used to measure change over time. An 82% follow-up rate was achieved on the original group of 79 clients, similarly a follow-up rate of 100% was also achieved for the selected group of 20 clients who were interviewed three times. Regardless of category of client, findings demonstrate an improvement over time for the outcome variables, general attitude to offending, anticipation of re-offending and perception of current life problems. However, the study failed to demonstrate any significant change for the outcome variables victim hurt denial and evaluation of crime as worthwhile. These results were short lived for many prisoners, who failed to sustain the gains made. Interviews with the cohort of 20 who underwent stage III interviews possibly suggest that those clients who did not receive continuity of treatment post programme, in terms of case management and structured treatment, did not fare as well as those who did.
PUBLISHED
Keywords: Drug use; case management; offending behaviour; group work; crime; outcome evaluation; prison; treatment